Therapeutic Effects of Topical Application of Lycium barbarum Polysaccharide in a Murine Model of Dry Eye - Qin, Danyi; Deng, Yingping; Wang, Lixiang; Yin, Hongbo (Frontiers in Medicine, 2022)
Purpose: To evaluate the safety and efficacy of Lycium barbarum polysaccharide (LBP) eye drops in a murine model of dry eye disease (DED). Methods: Six- to eight-week-old female C57BL/6 mice were subjected to a combination of desiccating stress (DS) and topical benzalkonium chloride (BAC) to induce DED. Five microliters of LBP eye drops (0.625 mg/ml, 2.5 mg/ml, or 12.5 mg/ml) or PBS was applied topically 3 times per day for 10 days to subsequently test their efficacy. Tear secretion, tear breakup time (TBUT), corneal irregularity, and corneal fluorescein staining scores were measured on days 3 and 10 after treatment. The expression of tumor necrosis factor-alpha (TNF-α) in the cornea was assessed by quantitative (q) RT–PCR on days 10. The ocular irritation of LBP eye drops of corresponding concentrations was evaluated on ten- to twelve-week-old female Sprague–Dawley rats. Results: Compared with PBS-treated groups, mice treated with 0.625 mg/ml, 2.5 mg/ml, and 12.5 mg/ml LBP showed a significant improvement in the clinical signs of DED in a dose-dependent manner, including corneal epithelial integrity, corneal regularity, and tear production, as well as significant inhibition of inflammatory cell infiltration and TNF-α expression levels in the cornea. All corresponding concentrations of LBP eye drops revealed no obvious ocular irritation. Conclusions: Topical application of LBP could ameliorate dry eye in a murine model of DED without obvious ocular irritation.